Menjaga Kesehatan Reproduksi Perempuan Dalam Al-Qur’An - ainaya muna (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
Reproductive health is a healthy condition that includes reproductive systems, functions and processes. Reproductive health for women is very important to pay attention to because it is closely related to the process of forming a family. Women must maintain their reproductive health so that they are protected from all infections or diseases that attack the reproductive organs. In Islam, reproductive health is also related to the mechanisms of the reproductive system itself which includes menstruation, pregnancy, breastfeeding, promiscuous sex (zina), and abortion. This research discusses issues regarding verses related to women's reproductive health. The aim is to find out the role of women in maintaining their reproductive health. The method used in this research is thematic interpretation research technique. Then at this point the discussion is motivated by the interpretation of the Al-Qur'an using the theory of Maudhu'i interpretation, namely; collects verses from the Qur'an that touch on the theme of reproductive health. The conclusion of this research is that the interpretation of verses on women's reproductive health includes the prohibition of sexual relations during menstruation, the prohibition of adultery, and the prohibition of having an abortion. So this can be interpreted by interpreters as support that it is true that the Qur'an pays attention to women's reproductive health. Thus, the verses about women's reproductive health can be understood as a form of understanding in maintaining reproductive health.